Environmental education at Geopark Araripe: contribution to the teaching of geography (Research, Society and Development, 2022)
Environmental Education at GeoPark Araripe is based on an attempt to strengthen visions of integration and interdisciplinarity that encourage a systematic reflection on socio-environmental diversity within its territory. In this sense, the first step to carry out these actions is to identify the representations about them involved in the educational process, participating in promoting the exercise of citizenship and improving the quality of life. Environmental Education at GeoPark Araripe has a great diversity of experiences, reflections and commitments, which have in common the transformation and awareness of society through “education”, the expansion of the ideals of Environmental Education is a challenge, without a doubt goals that will only be achieved in the medium and long term. The main objective of this research is to realize the valuable contribution that GeoPark Araripe provides for the teaching of geography through Environmental Education, it is characterized as a qualitative research, as it is a research that aims to know and interpret aspects and characteristics of the theme and of the studied group.